BAY 94‐9027, a PEGylated recombinant factor VIII, exhibits a prolonged half‐life and higher area under the curve in patients with severe haemophilia A: Comprehensive pharmacokinetic assessment from clinical studies. Issue 5 (2nd July 2018) - Shah, A.; Coyle, T.; Lalezari, S.; Fischer, K.; Kohlstaedde, B.; Delesen, H.; Radke, S.; Michaels, L. A.
Abstract : Introduction: Recombinant factor VIII (rFVIII) products with extended half‐lives, such as BAY 94‐9027, can potentially maintain higher FVIII levels for longer periods of time, thus providing improved bleeding protection vs standard‐acting FVIII products. Aim: To characterize the pharmacokinetic (PK) profile of BAY 94‐9027 from phase 1, phase 2/3 (PROTECT VIII) and phase 3 (PROTECT VIII Kids) clinical trials in adults, adolescents and children with severe haemophilia A Methods: Patients with severe haemophilia A (FVIII <1%) with >50 FVIII exposure days (EDs) and no history of inhibitors were included in the phase 1 (18–65 years, ≥150 EDs), PROTECT VIII (12–65 years, ≥150 EDs) and PROTECT VIII Kids (<12 years, >50 EDs) trials. PK parameters were assessed following a 25‐IU/kg or 60‐IU/kg BAY 94‐9027 dose in the phase 1 study after the first and repeated infusion, in PROTECT VIII after the first and repeated 60‐IU/kg infusion and in PROTECT VIII Kids after a single 60‐IU/kg infusion. The chromogenic assay was used to assess FVIII activity. Results: Compared with sucrose‐formulated rFVIII, BAY 94‐9027 had reduced clearance that resulted in a ~1.4‐fold increase in half‐life and dose‐normalized area under the curve (AUC). The BAY 94‐9027 PK profile was comparable after single‐ and repeated‐dose administrations. Dose‐proportional increases were observed between 25‐ and 60‐IU/kg administrations. BAY 94‐9027 PK characteristics were age dependent, consistent with other FVIII products. Conclusions: BAY 94‐9027 shows an extended half‐life and increased AUC vs standard‐acting FVIII products. These PK characteristics will result in higher FVIII levels for longer duration.